1983
DOI: 10.3109/03009748309102002
|View full text |Cite
|
Sign up to set email alerts
|

Bioflavonoid-Mediated Stabilization of Collagen in Adjuvant-Induced Arthritis

Abstract: In rats with adjuvant-induced arthritis, the effect of (+)-catechin (CA) and 0-(beta-hydroxyethyl) rutosides (HR) on the crosslinking of collagen was studied. Compared with controls the arthritic group showed an increase in the reversibility of neutral salt-soluble collagen gel, solubility of acid-insoluble collagen to denaturing agents and the ratio of alpha/beta subunits of neutral salt-soluble collagen. These results suggest an impaired maturation of collagen in arthritic animals. Administration of CA or HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
(14 reference statements)
0
10
0
1
Order By: Relevance
“…PA from cranberry inhibited the surface-adsorbed gluocsyltransferases and F-ATP activities, and the acid production by Streptococcus mutans (23). Studies have also shown that PAs increased collagen synthesis and accelerated the conversion of soluble collagen to insoluble collagen during development (24, 25). PA-treated collagen matrices were demostrated to be nontoxic and resisted enzyme digestion in vitro and in vivo (26).…”
Section: Introductionmentioning
confidence: 99%
“…PA from cranberry inhibited the surface-adsorbed gluocsyltransferases and F-ATP activities, and the acid production by Streptococcus mutans (23). Studies have also shown that PAs increased collagen synthesis and accelerated the conversion of soluble collagen to insoluble collagen during development (24, 25). PA-treated collagen matrices were demostrated to be nontoxic and resisted enzyme digestion in vitro and in vivo (26).…”
Section: Introductionmentioning
confidence: 99%
“…Proanthocyanidins (PAs) are widespread in fruits and vegetables and belong to the category known as condensed tannins, which consist of highly hydroxylated structures capable of forming insoluble complexes with carbohydrates and protein 27, 28. Available evidence shows that PAs increase collagen synthesis and accelerate the conversion of soluble collagen to insoluble collagen during development 29. Han et al30 have investigated the cytotoxicity, crosslinking rate, and biocompatibility of PAs as collagen tissue fixative.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical cross-linkers have been reported to further stabilize collagen fibrils in several connective tissues (Rao et al, 1983;Cheung et al, 1990;Sung et al, 1999;Ritter et al, 2001;Han et al, 2003;Bedran-Russo et al, 2007). Glutaraldehyde, a widely used synthetic cross-linker, can enhance collagen stability; however, it presents some drawbacks, such as toxicity (Cheung et al, 1990;Southern et al, 2000).…”
Section: Introduction Tmentioning
confidence: 99%